2011
DOI: 10.1002/pola.24683
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization mechanism of trimethylene carbonate carried out with zinc(II) acetylacetonate monohydrate

Abstract: The proposed mechanism of initiation and course of ring‐opening polymerization of cyclic trimethylene carbonate (TMC) involving zinc(II) acetylacetonate is in accordance with the mechanism of monomer activation. At the first stage of the process, coordination of carbonate to Zn(Acac)2·H2O complex occurs with the release of weakly coordinated water molecules. This free water molecule reacts with active TMC–Zn(Acac)2 complex. The reaction results in the formation of propanediol and CO2 emission. During further s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…2). Zinc oxide probably catalysed both the formation of 375 cyclic carbonates but also its polymerization in agreement with Pastusiak et al [41] On the contrary, 376 polymerization products were not found in any other reaction mixtures were five and seven-members cyclic 377 carbonates were formed. 378…”
Section: Fig 2 Here 363supporting
confidence: 82%
“…2). Zinc oxide probably catalysed both the formation of 375 cyclic carbonates but also its polymerization in agreement with Pastusiak et al [41] On the contrary, 376 polymerization products were not found in any other reaction mixtures were five and seven-members cyclic 377 carbonates were formed. 378…”
Section: Fig 2 Here 363supporting
confidence: 82%
“…The choice of the type of initiator was based on the availability and stability of these compounds, facilitating the widespread use not only in the laboratory conditions. The choice were also based on the earlier exploratory studies and other published results on the polymerization and copolymerization of cyclic carbonates where zinc acetylacetonate and lanthanum compounds were as a single component initiator, exhibited high efficiency in this type of reactions. During application of these compounds, intramolecular transesterifications were rather insignificant.…”
Section: Resultsmentioning
confidence: 99%
“…In the first stage of the lactide, glycolide and TMC terpolymers synthesis hydroxyl terminated oligocarbonates were obtained by ROP of TMC [Scheme 1(A)], according the monomer activation mechanism. 26 In brief, into a glass reactor with a capacity 50 cm 3 , connected to a vacuum line and equipped to bring the dried argon 10.2 g (0.1 mol) TMC, 0.2 g (2.2 3 10 23 mol) 1,4-butanediol (initiator), and 0.01 g low toxic zinc (II) acetylacetonate monohydrate as a catalyst were introduced. The reaction mixture was stirred under an argon atmosphere at 1208C for 3 h. Properties of obtained oligomer OL1 are shown in Table I.…”
Section: Copolymer Synthesis and Characterizationmentioning
confidence: 99%